Relações precárias em cooperativas de trabalho: estudo de caso em Pelotas - RS - Mayer, Jair Alberto (2009)
This study analyses the constitution and action of a work cooperative and its internal relationships in Pelotas City, Rio Grande do Sul, Brazil. It was questioned the role of work cooperatives in the process of disorganization of formal paid employment and terceirization in several productive activities which demand some intensive and smaller professional qualification labour from workers´ experiences in everyday work in the cooperative. It also covers an analysis of neoliberal politics consequences on building identities of the working class and their repercussion on workers´ trade union organizations. At last it evaluates workers´ trade unions actions in relation to the terceirization process of work relations and to the cooperative.